Rancang Bangun Alat Pengasapan Ikan dengan Metode Pengasapan Panas (Hot Smoking) dan Pengasapan Dingin (Cold Smoking) - Emai Rizkita Br Karo; Indah Widanarti; Yosefina Mangera (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
The purpose of this study was to produce a fish smoking device for hot smoking and cold smoking methods. This study used 3 types of fish, namely paha fish (Leptobrama sp.), stingray (Dasyatis sp.), and tilapia fish (Oreochromis mossambicus), and the fuel used as fuel for smoking is coconut shell. The data measured included smoking room temperature data, fish weight before and after smoking. The data obtained were analyzed descriptively. The results showed that smoking fish using hot smoking and cold smoking methods with specifications, length 50 cm, width 50 cm, overall height 83 cm. This tool consists of three main components, namely, a fumigation chamber which is combined with a hot smoking biomass combustion chamber, a cold smoking biomass combustion chamber and a connecting pipe. The performance test of the tool was carried out by calculating the weight loss of fish during hot smoking and cold smoking. The smoking time used for hot smoking is 2 hours (temperature 50 – 75℃) and cold smoking 4 hours (30 – 45 ℃). The results showed that the highest percentage of weight loss during hot smoking occurred in stingrays on the second shelf, which was 29.25%, while the highest percentage of weight loss during cold smoking occurred in stingrays on the first shelf, which was 23.79%. The weight loss of fish in both hot and cold smoking is strongly influenced by the smoking time, the distance between the smoking rack and the heat source and the type of fish. Keywords : cold, heat, shrinkage, smoking, weight